Exploring Curriculum for the Integration of Disaster Risk Reduction and Climate Change: The Case of Planning Schools in India - Roy, Anil K.; Kaliyath, Ajith; Ghosh, Debjani (Environment and Urbanization ASIA, 2022)
This article explores the urban planning curriculum of the three selected planning schools in India. They are the School of Planning and Architecture (SPA), New Delhi; Department of City and Regional Planning, Indian Institute of Technology (IIT), Kharagpur; and the Faculty of Planning, CEPT University, Ahmedabad. It uses content analysis to understand the deepening of research, skill formation and the possible change in pedagogy due to growing concerns about climate change (CC) and disaster risk reduction (DRR) in the urban area. The concerned programme coordinators and heads of the departments have also been consulted to find out the general approach to integrating CC and DRR knowledge into their planning curricula. An account of research outreach of faculty members, student dissertations and institutional publication in the CC and DRR has also been presented to illustrate research outreach with the community. It has been found that these schools need to deepen further their engagement with the domain of CC and DRR.
openalex: W4306318284
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:disaster risk reduction; oa:keyword:planning schools; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T10930 Global Flood Risk Assessment and Management; openalex:import; openalex:yes